ST-351: Distribution Theory-I - Malati C. Yeola (ST-351: Distribution Theory-I, 2023)
In this book of distribution theory, probability density functions of different distributions are defined and their properties are studied. It explains the important operations on distributions, such as obtaining mean, median, skewness etc. This book serves as a comprehensive introduction to distributions like beta and Cauchy.It also includes order statistics, Chebychev’ inequality, central limit theorem and weak law of large numbers. It explores the mathematical foundations of distributions, their algebraic properties, and their convergence properties. In addition to the foundational aspects, the book explores various applications of distribution theory. The book includes numerous examples, exercises.